2011
DOI: 10.1097/dad.0b013e3181f7d397
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Langerhans Cell Concentration in Lichen Planopilaris and Traction Alopecia With Possible Immunologic Implications

Abstract: Lichen planopilaris and long-standing traction alopecia are both traditionally classified as scarring alopecias. The etiology of lichen planopilaris has not been fully elucidated, although an autoimmune mechanism is generally accepted with Langerhans cell involvement implicated in previous studies. The etiology of traction alopecia is generally considered to be the result of mechanical force with subsequent inflammation without an autoimmune component. Langerhans cells in pure traction alopecia have not been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
1
14
0
2
Order By: Relevance
“…46 This is in accordance with past studies. 47 These data support a role for Langerhans cells in the stimulation of the cytotoxic response to the follicular bulb region.…”
Section: Alopecia Areatasupporting
confidence: 94%
See 1 more Smart Citation
“…46 This is in accordance with past studies. 47 These data support a role for Langerhans cells in the stimulation of the cytotoxic response to the follicular bulb region.…”
Section: Alopecia Areatasupporting
confidence: 94%
“…44 The ratio of Langerhans cells to T cells has been evaluated in LPP and traction alopecia with the use of CD1a and CD3 immunostains, respectively. 46 Traction alopecia was selected as a control tissue probably because inflammation is not directly involved in its pathogenesis opposed to the primary lymphocytic cicatricial alopecias as LPP. It was found that the mean ratio is significantly higher in LPP (1.28) as compared with traction alopecia (0.59).…”
Section: Cd1a For Langerhans Cells Lichen Planopilarismentioning
confidence: 99%
“…Additionally, studies regarding etiopathogenesis in LPP showed that CD1a-positive Langerhans cells moderate inflammation and may serve as the causative immune cell. 20 There was also a statistically significant decrease in the frequency of T reg in AA vs ISK, which was used as an example of an inflammatory T reg frequency in inflammatory dermatoses, 13 there was also considerable variation in the frequency of T reg among the specimens within the ISK specimens. The frequency seemed to positively correlate with the level of inflammation present, with specimens with mild inflammation having the lowest frequency of T reg and specimens with severe inflammation having the highest frequency of T reg .…”
Section: Discussionmentioning
confidence: 96%
“…This difference is not unexpected as AA and LPP represent two distinct subtypes of alopecia with different histological findings. Additionally, studies regarding etiopathogenesis in LPP showed that CD1a‐positive Langerhans cells moderate inflammation and may serve as the causative immune cell …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation